The evolution of Romanian demographic phenomena in terms of globalization - BĂLAN, Mariana; VASILE, Emilia (Annals of Spiru Haret University. Economic Series, 2010)
Globalisation and demography are the main forces modelling the development of societies at large and of each nation in particular. The paper aims to identify and synthetically present some factors of influence which triggered by the end of the 20th century and the beginning of the 21st century a series of characteristics defining the changes of the demographic model and structure of population on age brackets. The paper presents the results obtained by using the Markov-type model, for studying the development of demographic indicators in Romania, and their forecasting as well.